ANALISIS PENGARUH INFLASI DAN NILAI TUKAR RUPIAH TERHADAP RETURN SAHAM (Studi Kasus Pada Perusahaan Otomotif dan Komponennya Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2018) - Nova Delta, Agnes; Panjaitan, Fery; Ruben Manullang, Rizal (Jurnal Akuntansi Bisnis Dan Keuangan, 2019)
This study aims to determine the effect of inflation and the rupiah exchange rate on stock returns in automotive manufacturing companies and their components. This research was obtained by purposive sampling method based on the criteria of 8 companies from a population of 13 companies. This research uses the multiple regression method with a significance level of 5% showing that partially the inflation variable does not have a significant effect between inflation on stock returns. this is evidenced in the t test explaining that each increase of 1 inflation results in 1% of stock returns, assuming the value of the intercept is 0. The results of the study also prove that there is no significant effect between the rupiah exchange rate on stock returns. this is evidenced in each 1% increase in stock returns has increased by 3.872% and the results of the study indicate that there is no significant effect between inflation and the rupiah exchange rate on stock returns. this can be seen from the sign value of 0.0443. thus the decision is clearly accepted H, and rejected H because 0.0443> 0.05.